Development of an EnergyEfficient Microclimate System for Dairy Herd Loose Keeping - I. M. Dovlatov; S. S. Yurochka (Сельскохозяйственные машины и технологии, 2021)
The authors studied the scientific and technical literature regarding the microclimate influence on dairy cattle productivity. It was found out that the building microclimate parameter deviation from certain limit values reduces milk yield by 10-20 percent decrease the live weight gain by 20-30 percent increases the mortality of young animals by 5-40 percent and reduces the number of lactations by 15-20 percent for the herd. (Research purpose) To conduct a survey of modern microclimate systems and their technical implementation for livestock buildings, suggesting the best option while reducing energy costs. (Materials and methods) A classification scheme was provided for microclimate systems. The factors affecting the microclimate of livestock premises were presented in one figure. The main functions of ventilation systems in animal husbandry were identified. The conditions for the use of natural and forced (tunnel) ventilation systems were described. The devices for changing the microclimate on the premises were presented. The possibility of using an overlapped ridge in the area of the roof ridge was considered to catch the airflow and minimize moisture penetration. (Results and discussion) To decrease energy consumption, it was proposed to shift from a supply ventilation system to a natural and hybrid ventilation system, which contains an air removal system, lighting equipment, heating elements, sensors, fans with spray nozzles, sashes. (Conclusions) It was found out that in summer, natural ventilation is unable to prevent heat stress from cows. It was determined that in case of heat stress within 60 days, losses could amount to 4.2 million rubles. To ensure optimal microclimate conditions and reduce costs from heat stress, it was proposed to use an innovative natural and hybrid ventilation system. The calculations showed that a 60-day energy consumption of  the proposed system equals 264 thousand rubles.